Understanding pilots’ cognitive processes for making in-flight decisions under stress - Li, Wen-Chin; Harris, Don; Hsu, Yueh-Ling; Wang, Thomas (Cranfield University, 2011)
In flight operations, pilots are confronted with many problems that occur in continually changing situations that create a level of stress and lead to accidents. To make rapid decisions, pilots make decisions using a holistic process involving situation recognition and pattern matching. This research investigated 157 pilots from a B747 fleet to find out how pilots make in-flight decision in such stressful situations. The research method is based upon evaluating the situational awareness, risk management, response time and applicability of four different decision-making mnemonics in six in-flight scenarios. The data obtained in this research suggests that the FOR-DEC may be suitable as a basis for providing training which will be applicable for covering all basic types of decision. FOR-DEC was evaluated as the most applicable mnemonic-based decision making process across the six different scenarios used. It also had significantly superior performance compared with the other three mnemonic-based methods evaluated (SHOR, PASS & DESIDE) when making recognition-primed decisions, response selection decisions, non-diagnostic procedural decisions, and problem-solving decisions.
Keywords: Accident Prevention, Aeronautical Decision-making, Human Errors, Stress, Time Pressure